Cobalamin-Mediated Electrocatalytic Reduction of Ethyl Chloroacetate in Dimethylformamide. Issue 5 (1st May 2022) - Gerroll, Benjamin H. R.; Lewis, Jared C.; Baker, Lane A.
Abstract : The catalytic reduction of ethyl chloroacetate (ECA) by hydroxocobalamin (HOCbl) in dimethylformamide was studied electrochemically and spectroelectrochemically to identify initial steps in the reaction between the electrogenerated Co(I) center of cobalamin (cob(I)alamin) and ECA. Cyclic voltammograms of HOCbl in the presence of ECA show a small increase in current related to reduction of Co(II) to Co(I), and a new peak at more negative potentials related to reduction of an ethyl carboxymethyl-Cbl intermediate. The oxidation state of HOCbl during catalysis was monitored by means of spectroelectrochemical controlled-potential bulk electrolysis. Addition of ECA to electrogenerated cob(I)alamin initially generates the Co(II) form (cob(II)alamin) followed by a gradual formation of an ethyl carboxymethyl-Cbl intermediate. Controlled-potential bulk electrolysis was performed to identify products formed from catalytic reduction of ECA by electrogenerated cob(I)alamin and quantify the number of electrons transferred per molecule of ECA. Product distributions and coulometric results, together with the results of voltammograms and spectroelectrochemical controlled–potential bulk electrolysis, were interpreted to propose a reaction mechanism.